“He’d seen it in the words of Owen and Brooke”: The Influence of Great War Poetry on Post-Millennium Soldier Poets - Felix Behler (Anglica. An International Journal of English Studies)
To this day, the term “soldier poetry” is still predominantly associated in popular perception with the 1914–1918 trench poets, such as Wilfred Owen, Siegfried Sassoon, or Isaac Rosenberg. And yet, the dawn of the new millennium, marked by the rise of the global War on Terror, saw a significant revival of the genre in Britain. One of the most noteworthy indicators of this is John Jeffcock’s anthology Heroes (2011), which has collected a hundred poems written by British soldiers who fought in recent conflicts – Iraq and Afghanistan in particular. While these poems are framed within the shifting military, socio-demographical, and political dimensions of war in our time, they simultaneously exhibit strong roots within the context of a specific literary tradition that originated in the First World War. This article sets out to analyse a selection of poems from Heroes, focusing on the way these poets construct a network of intertextual citations, borrowings, and allusions to connect their texts – quite deliberately – with the much acclaimed generation of poets form the Great War. The article argues that, by doing so, the poets facilitate the transposition of a set of broader myths and emotions that are typically associated with the Great War onto the new (con)text, thereby adding new literary, cultural, and social meanings to the texts.